Potential application of Northern Argentine propolis to control some phytopathogenic bacteria - Ordóñez, Roxana Mabel (2011)
The antimicrobial activity of samples of Northern Argentine propolis (Tucumán, Santiago del Estero and Chaco) against phytopathogenic bacteria was assessed and the most active samples were identified.Minimal inhibitory concentration (MIC) values were determined by agar macrodilution and broth microdilution assays. Strong antibacterial activity was detected against Erwinia carotovora spp carotovora CECT 225, Pseudomonas syringae pvar tomato CECT 126, Pseudomonas corrugata CECT 124 and Xanthomonas campestris pvar vesicatoria CECT 792. The most active propolis extract (Tucumán, T1) was selected to bioguide isolation and identified for antimicrobial compound (2′,4′-dihydroxychalcone). The antibacterial chalcone was more active than the propolis ethanolic extract (MIC values of 0.5-1μgml -1 and 9.5-15μgml -1, respectively). Phytotoxicity assays were realized and the propolis extracts did not retard germination of lettuce seeds or the growth of onion roots. Propolis solutions applied as sprays on tomato fruits infected with P. syringae reduced the severity of disease. Application of the Argentine propolis extracts diluted with water may be promising for the management of post harvest diseases of fruits.